2021
DOI: 10.1039/d1ra05055a
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol-derived polyelectrolyte–protein nanoclusters for protein drug delivery

Abstract: Polyethylene glycol-derived polyelectrolyte–protein nanoclusters were synthesized based on electrostatic complexation for protein drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…At the same time, the nanodelivery system can also improve protein solubility and bioavailability, improve treatment effectiveness and reduce side effects. 116 Zhao and colleagues studied an injectable hydrogel composed of ADA, doxorubicin (DOX), tricarboxylic acid (BTC), and sodium alginate. 117 In the tumor microenvironment, the synergistic action of DOX and BTC promoted ATP induction, while ADA catalyzed the conversion of adenosine to inosine, resulting in a significant antitumor effect.…”
Section: Nanoparticles Targeting the Adenosine Pathway For Cancer Imm...mentioning
confidence: 99%
“…At the same time, the nanodelivery system can also improve protein solubility and bioavailability, improve treatment effectiveness and reduce side effects. 116 Zhao and colleagues studied an injectable hydrogel composed of ADA, doxorubicin (DOX), tricarboxylic acid (BTC), and sodium alginate. 117 In the tumor microenvironment, the synergistic action of DOX and BTC promoted ATP induction, while ADA catalyzed the conversion of adenosine to inosine, resulting in a significant antitumor effect.…”
Section: Nanoparticles Targeting the Adenosine Pathway For Cancer Imm...mentioning
confidence: 99%
“…Compared with small-molecule drugs, protein drugs have become a hot field of new drug development because of their high activity, high specificity, low physiological toxicity and good biocompatibility. However, the unique molecular structure and biochemical characteristics rapidly inactivate protein drugs in complex biological environments, which limits their application to biomedicine ( Yu Y. et al, 2021 ). It has been shown that nanocomposite hydrogels can encapsulate protein drugs in their internal network structure, thus protecting them from the external environment ( Li M. et al, 2017 ; Wang Z. et al, 2019 ; Zhou et al, 2022 ).…”
Section: Application Of a Nanocomposite Hydrogel Delivery System To D...mentioning
confidence: 99%